RETRACTED: Integration of Neuroscience and Entrepreneurship: A Systematic Review and Bibliometric Analysis - Liu, Weiwei; Xu, Yimeng; Xu, Tiantian; Ye, Zijian; Yang, Jiani; Wang, Yan (Frontiers in Psychology, 2022)
In this study, we investigate the integration between neuroscience and entrepreneurship. This study proposes two research directions. First, we have given a direction to understand the concept of neuro-entrepreneurship, as well as this study demonstrates how researchers can investigate the neuro-entrepreneurship using scientific research methods. Second, we try to build a road map for entrepreneurial researchers to provide directions for entering neuro-entrepreneurship research. However, this is a newly-emerging research area in the field of entrepreneurship. Therefore, to better analyze the dynamics of the research trends, we used the bibliometric method to capture the pattern of current publications on the subjects related to neuro-entrepreneurship. We examined the published papers on the keywords of “neuroscience” and “entrepreneurship” or “neuro-entrepreneurship” from 2000 to 2021. To identify the keywords, we used two well-known academic databases (social science citation index (SSCI) and science citation index databases) from the Web of Science (WOS) database. The used three keywords were adopted from the past studies that integrate neuroscience with entrepreneurship. After carefully reviewing the well-known academic research papers, it is observed that neuro-entrepreneurship is a novel research area. The outcomes of this study provide the track for the researchers to describe the theoretical connection between neuroscience and entrepreneurship. The findings also suggest that experimental design and neuroimaging techniques are the core constituents of neuro-entrepreneurship research. In the future, such kind of study can be empirically investigated.